THE IMPORTANCE OF STRESS MANAGEMENT EDUCATION IN ISLAMIC BOARDING SCHOOLS: EFFORTS TO IMPROVE THE MENTAL HEALTH OF STUDENTS - Zahro, Fatimatus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of the research was to find out how big a role stress management plays in the stability of students. Where life in various Islamic boarding schools demands that students behave independently and are trained to do several things independently too. The research was conducted at the Nurul Jadid Islamic Boarding School using a case study type qualitative research method. Data collection techniques are interviews, observation and documentation. The results of the research show that students who are predominantly teenagers are very vulnerable to mental health disorders. This is because the students are still in the learning process with a quite busy schedule. The role of foster carers in providing assistance to students greatly influences the development of the students' condition, especially in Mental Health. Several activities and policies are carried out by central and regional Islamic boarding school administrators to implement stress management for students in the hope that students will continue to participate in all Islamic boarding school activities well.